2012
DOI: 10.1016/j.forsciint.2011.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CYP2D6 genotype on the disposition of the enantiomers of venlafaxine and its major metabolites in postmortem femoral blood

Abstract: However, a substantial variation in the relationship between the S-and R-enantiomers of VEN and metabolites was evident (S/R ratios ranging from 0.23-17.6). In six cases, a low S/R VEN ratio (mean 0.5) was associated with a high S/R ODV ratio (mean 11.9). Genotyping showed that these individuals carried two inactive CYP2D6 genes indicating a poor metabolizer phenotype. From these data we conclude that enantioselective analysis of VEN and ODV can predict if a person is a poor metabolizer genotype/phenotype for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 61 publications
4
23
0
Order By: Relevance
“…A study that evaluated the association of CYP2D6 genotype with the dose-related effects of VEN demonstrated that patients who lacked a fully active CYP2D6 allele were not able to tolerate a maintenance dosage higher than 75 mg/day when compared to patients with at least one fully active 2D6 allele [95]. In the same way, other research works suggested that a CYP2D6 PM status [genotyping (two inactive alleles; *3-*8, *11-*16, *19-*21, *38, *40, *42) or phenotyping determined] increases the risk of developing side effects [37,38,62,63,77,96,97]. Nevertheless, as currently there are not enough data to allow estimation of dose adjustments, it is recommended selecting an alternative drug or adjusting dose to clinical response and monitoring VEN and ODV plasma concentrations.…”
Section: Genetic Biomarkers and Metabolic Phenotypesmentioning
confidence: 94%
See 1 more Smart Citation
“…A study that evaluated the association of CYP2D6 genotype with the dose-related effects of VEN demonstrated that patients who lacked a fully active CYP2D6 allele were not able to tolerate a maintenance dosage higher than 75 mg/day when compared to patients with at least one fully active 2D6 allele [95]. In the same way, other research works suggested that a CYP2D6 PM status [genotyping (two inactive alleles; *3-*8, *11-*16, *19-*21, *38, *40, *42) or phenotyping determined] increases the risk of developing side effects [37,38,62,63,77,96,97]. Nevertheless, as currently there are not enough data to allow estimation of dose adjustments, it is recommended selecting an alternative drug or adjusting dose to clinical response and monitoring VEN and ODV plasma concentrations.…”
Section: Genetic Biomarkers and Metabolic Phenotypesmentioning
confidence: 94%
“…Although VEN is not yet clinically available as a single enantiomer, but instead as a racemic mixture, it is consensual that O-demethylation reactions occur with strong stereoselectivity towards the R-enantiomer [61][62][63], and these type of reactions are predominantly mediated by CYP2D6; N-demethylation reactions appear to be at least partially mediated via CYP3A4 [1,8,28,45,63]. As expected, a recent review refers that CYP2D6 poor metabolizers (PMs) have significantly lower plasma levels of ODV and higher levels of VEN as compared to extensive metabolizers (EMs) [38].…”
Section: Metabolic Pathwaysmentioning
confidence: 99%
“…A few studies have described a possible stereoselective metabolism of VEN to ODV with either selection toward the ( S ) isoform [4,5] or the ( R ) isoform [7,8], but the majority of studies on VEN pharmacokinetics and antidepressant response in association with the CYP2D6 metabolizer phenotype do not distinguish between the enantiomers (Table 1). …”
Section: Pharmacokineticsmentioning
confidence: 99%
“…A literature screening has shown that separation techniques, for example, HPLC [5][6][7][8][9][10][11], LC [4,12,13], and GC [14], are commonly used for the simultaneous determination of VEN and ODV in biological materials. Furthermore, CE [15] and CEC [16] were also used for this purpose.…”
Section: Introductionmentioning
confidence: 99%